2013
DOI: 10.1172/jci66024
|View full text |Cite
|
Sign up to set email alerts
|

Cancer stem cells in the development of liver cancer

Abstract: Liver cancer is an aggressive disease with a poor outcome. Several hepatic stem/progenitor markers are useful for isolating a subset of liver cells with stem cell features, known as cancer stem cells (CSCs). These cells are responsible for tumor relapse, metastasis, and chemoresistance. Liver CSCs dictate a hierarchical organization that is shared in both organogenesis and tumorigenesis. An increased understanding of the molecular signaling events that regulate cellular hierarchy and stemness, and success in d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
442
1
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 474 publications
(450 citation statements)
references
References 155 publications
3
442
1
4
Order By: Relevance
“…Some studies have indicated the importance of evaluating ''stemness'' in HCC; it reflects the malignant nature of the tumor and closely correlates with a poor prognosis after surgery [9][10][11][12]. Recent evidence has also suggested that HCC may conform to the cancer stem cell (CSCs) hypothesis, which proposes that a subset of cells with stem cell features play a fundamental role in tumor maintenance and chemo/radiation resistance [13]. CSCs, also called tumor-initiating cells or cancer stem-like cells, possess stem cell features in their self-renewal and differentiation capacity, and contribute to the formation of heterogeneous tumor cell populations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have indicated the importance of evaluating ''stemness'' in HCC; it reflects the malignant nature of the tumor and closely correlates with a poor prognosis after surgery [9][10][11][12]. Recent evidence has also suggested that HCC may conform to the cancer stem cell (CSCs) hypothesis, which proposes that a subset of cells with stem cell features play a fundamental role in tumor maintenance and chemo/radiation resistance [13]. CSCs, also called tumor-initiating cells or cancer stem-like cells, possess stem cell features in their self-renewal and differentiation capacity, and contribute to the formation of heterogeneous tumor cell populations.…”
Section: Introductionmentioning
confidence: 99%
“…CSCs, also called tumor-initiating cells or cancer stem-like cells, possess stem cell features in their self-renewal and differentiation capacity, and contribute to the formation of heterogeneous tumor cell populations. In HCC, several stem cell markers, including CD133, CD90, CD13, epithelial cell adhesion molecule (EpCAM), and CD24, have been reported to enrich side populations of CSCs [13][14][15]. We recently reported that the stem cell markers EpCAM and alpha-fetoprotein (AFP) can be used to classify HCC subtypes with distinct gene expression profiles and patient prognoses [11].…”
Section: Introductionmentioning
confidence: 99%
“…Chronic inflammation, often associated with liver injury, leads to secretion of cytokines, chemokines, free radicals, and other DNA‐damaging molecules, thereby changing the hepatic microenvironment 78. Persistent inflammation during this long‐term process leads to an expansion of hepatic stem and progenitor cells that accumulate genetic and epigenetic alterations.…”
Section: Tgf‐β In An Invasive Cancer Stem Cell Modelmentioning
confidence: 99%
“…Efforts have been made on classifying HCCs according to the status of gene mutations, chromosomal aberrations, gene/protein expression, and epigenetic modification in order to find hidden molecular features that can explain this heterogeneity [1,2]. The recent advances in molecular classification and the re-emergence of a cancer stem cell (CSC) hypothesis have highlighted the central role of stemness in HCC pathogenesis [3]. Moreover, sorafenib increased overall survival in a randomized controlled trial against placebo in advanced HCC, and tumor progression invariably occurred.…”
mentioning
confidence: 99%
“…In liver cell lineages, EpCAM is absent in mature hepatocytes but detectable in hepatic stem/progenitor cells and cholangiocytes [8]. Numerous studies have suggested the utility of EpCAM as a marker to identify liver cancer stem cells as well as normal hepatic progenitors [3]. In HCC, EpCAM-positivity correlates with a high frequency of vascular invasion, poor prognosis after surgical resection, and high infection rates with hepatitis B virus (HBV) [9].…”
mentioning
confidence: 99%